Search for a low-mass neutral Higgs boson with suppressed couplings to fermions using events with multiphoton final states - Aaltonen, T.; Amerio, S.; Amidei, D.; Anastassov, A.; Annovi, A.; Antos, J.; Apollinari, G.; Appel, J. A.; Arisawa, T.; Artikov, A.; Asaadi, J.; Ashmanskas, W.; et al. (My University, 2016)
A search for a Higgs boson with suppressed couplings to fermions, hf, assumed to be the neutral, lower-mass partner of the Higgs boson discovered at the Large Hadron Collider, is reported. Such a Higgs boson could exist in extensions of the standard model with two Higgs doublets, and could be produced via pp?H±hf?W?hfhf?4?+X, where H± is a charged Higgs boson. This analysis uses all events with at least three photons in the final state from proton-antiproton collisions at a center-of-mass energy of 1.96 TeV collected by the Collider Detector at Fermilab, corresponding to an integrated luminosity of 9.2 fb-1. No evidence of a signal is observed in the data. Values of Higgs-boson masses between 10 and 100 GeV/c2 are excluded at 95% Bayesian credibility. © 2016 American Physical Society.
Citation: Aaltonen, T., Amerio, S., Amidei, D., Anastassov, A., Annovi, A., Antos, J., . . . Zucchelli, S. (2016). Search for a low-mass neutral Higgs boson with suppressed couplings to fermions using events with multiphoton final states. Physical Review D - Particles, Fields, Gravitation and Cosmology, 93(11). doi:10.1103/PhysRevD.93.112010